1983
DOI: 10.1073/pnas.80.17.5435
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of tissue uptake of cholesterol ester from that of apoprotein A-I of rat plasma high density lipoprotein: selective delivery of cholesterol ester to liver, adrenal, and gonad.

Abstract: The metabolic fate of homologous high density lipoprotein (HDL) was studied in the rat, tracing the apoprotein A-I (apo A-I) and cholesterol ester moieties simultaneously. The apo A-I was labeled with covalently linked "MI-labeled tyramine cellobiose, which accumulates in the cells degradingthe apoprotein; [3H]cholesterol ethers, which cannot be hydrolyzed or mobilized after uptake, were incorporated into the lipid core of reconstituted HDL to reflect the fate of the cholesterol esters. Several lines of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
199
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(209 citation statements)
references
References 23 publications
8
199
0
2
Order By: Relevance
“…20 Others have similarly reported that HDL was degraded much less readily than LDL in cultured human fibroblasts 35 and in rat aortic smooth muscle cells. 38 In the study reported here, we found that, on average, the fraction of cell-associated 125 I-LDL that was degraded was about 4.4-fold greater than that of 125 I-HDL. This difference agreed well with that reflected by the lipoprotein clearance measurements.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…20 Others have similarly reported that HDL was degraded much less readily than LDL in cultured human fibroblasts 35 and in rat aortic smooth muscle cells. 38 In the study reported here, we found that, on average, the fraction of cell-associated 125 I-LDL that was degraded was about 4.4-fold greater than that of 125 I-HDL. This difference agreed well with that reflected by the lipoprotein clearance measurements.…”
Section: Discussionmentioning
confidence: 64%
“…The absolute amounts of 125 I-HDL recovered were too small to allow compositional analysis, but the increased density of the lipoprotein suggests the possible removal of lipids and subsequent release of lipid-depleted HDL. Recent observations of Glass et al 38 and Stein et al 39 are pertinent to this speculation. These workers, using HDL labeled with nonmetabolizable tracers, reported the selective hepatic uptake in rats of the labeled cholesterol ester analogue, compared to labeled HDL-apoprotein.…”
Section: Smentioning
confidence: 94%
“…HDL CE selective uptake is defined as the movement of CE from HDL into target cells without significant internalization and degradation of the HDL particle (Gwynne and Hess, 1980;Glass et al, 1983;Stein et al, 1983;Reaven et al, 1984;Glass et al, 1985;Pittman et al, 1987). This mechanism is distinct from that of the LDL receptor pathway, where LDL is internalized and the particle is degraded in the endosomal/lysosomal pathway (Brown and Goldstein, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…6 Subsequently, murine SR-BI was shown to mediate the uptake of lipid, but not apoprotein, from HDL into cells, 1 a process described as selective uptake. [7][8][9] This finding established SR-BI as the first HDL transmembrane receptor to be identified and cloned. Further studies of the human homologue demonstrated that it also is a multilipoprotein receptor that binds HDL, LDL, and VLDL.…”
mentioning
confidence: 99%